BILINGUAL EDUCATION AS SUCH DOES NOT AND CANNOT ALWAYS REPLACE SECOND LANGUAGE TEACHING FOR THE PURPOSE OF DEVELOPING SECOND LANGUAGE SKILLS WE SHOULD THINK OF BILINGUAL EDUCATION AND FOREIGN OR SECOND LANGUAGE TEACHING AS NATURAL ALLIES RATHER THAN ALTER - Ancira, Sara (Universidad Autónoma de Nuevo León, 2022)
Introduction lncreasingly, due to economic, social, cultural, and academic reasons proficiency in English is becoming a must in Monterrey, México. To meet this need the Universidad Autónoma de Nuevo León (UANL) has developed different English language programs which seek to promote the mastery of English among university students. Presently, the university is offering a program at the high-school level that integrates English language instruction into academic content instruction. This means that English language is used as the medium of instruction for science - biology, chemistry, physics- mathematics and computer science which are part of the official school currículum. English language, in this approach, becomes the vehicle for teaching and learning the specific knowledge of such academic subjects.